The Digital Economy and its Role in Attracting Foreign Direct Investment in the Arab Republic of Egypt - El Touni, Sherine (The Arab Journal of Administration, 2022)
The technological development that the world is witnessing has increased the importance of the communication and information technology sector, which has led to the emergence of modern concepts that were not known, perhaps the important of this is the digital economy , which has become the icon of development because of its great role in all fields, and countries are striving to improve it. Egypt has recognized its great importance and is seeking quickened steps towards its application, and it naturally has a clear impact, and an essential component of attracting foreign direct investment. This research aims to study the relationship between the digital economy and foreign direct investment in Egypt, by presenting a theoretical framework that clarifies the basic concepts of the two sides of the relationship (digital economy and foreign investment), then finding the relationship between them through a statistical study based on several variables, namely foreign direct investments as a dependent variable and indicators of the digital economy (fixed telephone and mobile phone subscriptions, the number of internet users and broadband service subscriptions) as an independent variable, during the period from 2005- 2018. The study relied on studying the chains of dependent and independent variables, in addition to integration tests between the independent variable and the dependent variables .The results showed that there is a positive relationship between the two parties to the study, although they differ in strength and influence from one indicator to another.